2008
DOI: 10.1186/1756-3305-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the acceptance of mass drug administration for the elimination of lymphatic filariasis in Agusan del Sur, Philippines

Abstract: Background: Mass drug administration (MDA) has been one of the strategies endorsed by the World Health Assembly for lymphatic filariasis (LF) elimination. Many factors, however, affect the acceptability of the MDA in the Philippines with acceptability defined as the ingestion of drugs -diethylcarbamazine and albendazole during MDA. These drugs were mainly distributed in fixed sites and mopping up activities were conducted through house-to-house visits to increase treatment coverage. The aim of conducting the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 5 publications
8
60
0
3
Order By: Relevance
“…In the Philippines and India the perceived benefit of the MDA was associated with compliance. Knowledge of LF was found to be linked to MDA compliance in the Philippines and in Haiti [27],[29]. A KAP survey conducted in Haiti in 2000 as well as follow-up survey in 2004 found that women were more likely to be noncompliant [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Philippines and India the perceived benefit of the MDA was associated with compliance. Knowledge of LF was found to be linked to MDA compliance in the Philippines and in Haiti [27],[29]. A KAP survey conducted in Haiti in 2000 as well as follow-up survey in 2004 found that women were more likely to be noncompliant [29].…”
Section: Discussionmentioning
confidence: 99%
“…The picture is similar in other areas of the world. Recent studies in the Philippines and the Colombo district of Sri Lanka found noncompliance rates of 30% and 28% [27],[28]. However, it is important to distinguish between noncompliance for a single or several MDA rounds and systematic noncompliance (never taking a drug for LF).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on LF and perceived benefits of antifilarial drugs were found to be associated with MDA acceptance ( P = 0.08). [11]…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the community's level of awareness about the disease and heightening their understanding of the benefits of the drugs and participation in MDA can lead to closure of the knowledgepractice gap, resulting in improved treatment coverage, behavioral change, and better control of schistosomiasis and other NTDs. 7,9,[18][19][20] To evaluate the impact of a health communication campaign for schistosomiasis control in western Kenya, we collected the perceptions of community health workers (CHWs) with regard to its impact on their ability to deliver praziquantel by MDA.…”
Section: Introductionmentioning
confidence: 99%